An Investigation of How Firm Size Affects Firm Value through Corporate Reputation - Fransiskus Eduardus Daromes; Robert Jao; Lukman Lukman; Rifaldy Wiasal (AKRUAL: JURNAL AKUNTANSI, 2022)
This study proves that firm size is an antecedent of corporate reputation in increasing firm value. Research model is constructed based on Resource-Based Theory. The populations used are manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2015-2018 period. The study uses purposive sampling method and documentary data from annual report and the Corporate Image Index score. Path analysis was used to analyze the data and the mediation hypothesis testing was carried out using Sobel test. The results show that the firm size has a significantly positive effect on corporate reputation, but insignificantly effect on firm value. Further testing shows that corporate reputation has a significantly positive effect on firm value. The Sobel test also proves that corporate reputation mediates the relationship between firm size and firm value. This research contributes to previous research studies related to corporate reputation, which tend to be examined partially what prompted the creation of corporate reputation and other parts of the partial ratings as well.